Impaired awareness in mesial temporal lobe epilepsy: Network analysis of foramen ovale and scalp EEG. Issue 12 (December 2021) - Varotto, Giulia; Burini, Alessandra; Didato, Giuseppe; Deleo, Francesco; Pastori, Chiara; Dominese, Ambra; Tringali, Giovanni; Panzica, Ferruccio; de Curtis, Marco; Di Giacomo, Roberta
Highlights: In mesial temporal lobe epilepsy implanted with foramen-ovale electrodes, connectivity is analyzed during seizures with and without impaired awareness. Impairment of awareness is related to network alterations occurring first in neocortical regions. The analysis of hub alterations can represent a suitable biomarker for scalp EEG-based prediction of awareness impairment. Abstract: Objective: We use co-registration of foramen-ovale and scalp-EEG to investigate network alterations in temporal-lobe epilepsy during focal seizures without (aura) or with impairment of awareness (SIA). Methods: One aura and one SIA were selected from six patients. Temporal dynamic among 4 epochs, as well as the differences between aura and SIA, were analyzed through partial directed coherence and graph theory-based indices of centrality. Results: Regarding the auras temporal evolution, fronto-parietal (FP) regions showed decreased connectivity with respect to the interictal period, in both epileptogenic (EH) and non-epileptogenic hemisphere (nEH). During SIAs, temporal dynamic showed more changes than auras: centrality of mesial temporal (mT) regions changes during all conditions, and nEH FP centrality showed the same dynamic trend of the aura (decreased centrality), until the last epoch, close to the impaired awareness, when showed increased centrality. Comparing SIA with aura, in proximity of impaired awareness, increased centrality was found in all the regions, except in nEH mT. Conclusions: Our findings suggested that the impairment of awareness is related to network alterations occurring first in neocortical regions and when awareness is still retained. Significance: The analysis of 'hub' alteration can represent a suitable biomarker for scalp EEG-based prediction of awareness impairment.